Divergent mononuclear cell participation and cytokine release profiles define hip and knee osteoarthritis - Grieshaber-Bouyer, Ricardo; Kämmerer, Till A.; Rosshirt, Nils; Nees, Timo A.; Schiltenwolf, Marcus; Hagmann, Sébastien; Moradi, Babak (Journal of Clinical Medicine, 2019)
Osteoarthritis (OA) is a progressive joint disease driven by a blend of inflammatory and biomechanical processes. Studies using human samples to understand inflammatory mechanisms in OA frequently recruit OA patients with different affected joints, even though recent evidence indicates that OA is a heterogeneous disease which only culminates in a common end point. Differences in age of onset and the dynamics of disease progression suggest that different joints may represent different disease entities, thereby diluting the discovery potential in a combined analysis. We hypothesized that different OA joints may also differ in immunopathology within the synovium. To investigate this hypothesis, we profiled the immune cell contribution (flow cytometry) and cytokine release profiles (ELISA) in purified synovial membrane mononuclear cells from 50 patients undergoing either hip (n = 34) or knee (n = 16) replacement surgery. Unsupervised computational approaches were used for disease deconstruction. We found that hip and knee osteoarthritis are not identical in respect to the inflammatory processes that take place in the synovial membrane. Instead, we report that principally CD14+ macrophages are expanded fourfold in the synovial membrane of patients with knee OA compared to hip OA, with a trend to higher expression in CD8+ T cells, while CD4+ T cells, B cells, and NK cells were found at comparable quantities. Upon isolation and culture of cells from synovial membrane, isolates from hip OA released higher concentrations of Eotaxin (CCL11), G-CSF, GM-CSF, INF-γ, IP-10 (CXCL10), TNF-α, MIP-1α (CCL3), MIP-1β (CCL4), IL-4, IL-10, IL-17, and lower concentrations of stem cell factor (SCF), thereby highlighting the difference in the nature of hip and knee osteoarthritis. Taken together, this study establishes hip and knee OA as immunologically distinct types of OA, and creates a resource of the cytokine expression landscape and mononuclear cell infiltration pattern of patients with hip and knee osteoarthritis.
Gesehen am 09.01.2020